CLASSICAL EQUIVALENCE OF LAMBDA-R-PHI-2 THEORIES - Accioly, A. J.; Wichoski, U. F.; Kwok, S. F.; Dasilva, NLPP (Iop Publishing Ltd, 1993)
It is shown that the action functional S[g, phi] = integral d4 x square-root -g[R/k(1 + klambdaphi2) + partial derivative(mu)phi partial derivative(mu)phi] describes, in general, one and the same classical theory whatever may be the value of the coupling constant lambda.